2016
DOI: 10.4143/crt.2016.187
|View full text |Cite
|
Sign up to set email alerts
|

Asian Consensus Guidelines for the Diagnosis and Management of Gastrointestinal Stromal Tumor

Abstract: Gastrointestinal stromal tumors (GISTs) are the most common mesenchymal tumors originating in the gastrointestinal tract. With the introduction of molecular-targeted therapy for GISTs which has yielded remarkable outcomes, these tumors have become a model of multidisciplinary oncological treatment. Although Western clinical guidelines are available for GISTs, such as those published by the National Comprehensive Cancer Network (NCCN) and the European Society of Medical Oncology (ESMO), the clinical situations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
202
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(209 citation statements)
references
References 72 publications
4
202
0
3
Order By: Relevance
“…Most recently, the Asian Consensus Guidelines (2016) for the Diagnosis and Management of GISTs was published to promote optimal care for Asian populations[51]. …”
Section: Current Treatment Guidelines For Gistsmentioning
confidence: 99%
“…Most recently, the Asian Consensus Guidelines (2016) for the Diagnosis and Management of GISTs was published to promote optimal care for Asian populations[51]. …”
Section: Current Treatment Guidelines For Gistsmentioning
confidence: 99%
“…For medical treatment, the Asian and Western guidelines are very similar in recommending first-line imatinib, second-line sunitinib, and third-line regorafenib, as described above [3,4,6,11]. However, most of the evidence supporting these recommendations has been established by clinical trials conducted in the Western countries, and Asian GIST patients may still require their own evidence for some aspects, such as dose optimization.…”
Section: Molecular Targeted Drug Therapy In Gistsmentioning
confidence: 99%
“…A systematic review of population-based cohort studies on GISTs showed that the incidence ranges from a low 0.43 per 100,000/year in the Shanxi Province, China, to a high 1.6-2.2 per 100,000/year in South Korea [4,5,6]. The cohort of 13,550 patients from 19 countries studied in this review gave the reported age as ranging from 10-100 years, with a median age in the 60s; both male and female populations had approximately equal distribution [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies have reported that small GIST of <2 cm in diameter may exhibit malignant potential, and this potential cannot be accurately assessed based on their size and location . Endoscopic ultrasound (EUS) can provide much information of the tumors, including their morphology, size, originating gastrointestinal wall layers, borders, and echogenicity; therefore, this technique has been recommended for detecting and staging submucosal neoplasms . Nevertheless, using conventional EUS, it is difficult to discriminate between GIST and benign subepithelial lesions, such as leiomyoma, and to determine the malignant potential of GIST.…”
Section: Introductionmentioning
confidence: 99%